Growth signalobody selects functional intrabodies in the mammalian cytoplasm - Lee, Songhee; Kaku, Yoshihiro; Inoue, Satoshi; Nagamune, Teruyuki; Kawahara, Masahiro (Biotechnology journal, 2016)
A versatile strategy to inhibit protein functions in the cytoplasmic environment is eagerly anticipated for drug discovery. In this study, we demonstrate a novel system to directly select functional intrabodies from a library in the mammalian cytoplasm. In this system, a target homo-oligomeric antigen is expressed together with a single-chain Fv (scFv) library that is linked to the cytoplasmic domain of a receptor tyrosine kinase (RTK) in the cytoplasm of murine interleukin-3 (IL-3)-dependent cells. As the tyrosine kinase is activated by dimerization, only scFv-RTK clones that can bind to the target antigen would be oligomerized and transduce a growth signal under the IL-3-deprived condition, which leads to selection of functional intrabodies. To demonstrate this system, we used rabies virus phosphoprotein (RV-P) that forms dimers in the cytoplasm as a target antigen. As a result, functional intrabodies were selected using our system from a naïve scFv library as well as from a pre-selected anti-RV-P library generated by phage display. This system may be applied for screening intrabodies that can prevent progression of various severe diseases.